A Catalytically Disabled Double Mutant of Src Tyrosine Kinase Can Be Stabilized into an Active-Like Conformation. Issue 6 (16th March 2018) - Meng, Yilin; Ahuja, Lalima G.; Kornev, Alexandr P.; Taylor, Susan S.; Roux, Benoît
Abstract: Tyrosine kinases are enzymes playing a critical role in cellular signaling. Molecular dynamics umbrella sampling potential of mean force computations are used to quantify the impact of activating and inactivating mutations of c-Src kinase. The potential of mean force computations predict that a specific double mutant can stabilize c-Src kinase into an active-like conformation while disabling the binding of ATP in the catalytic active site. The active-like conformational equilibrium of this catalytically dead kinase is affected by a hydrophobic unit that connects to the hydrophobic spine network via the C-helix. The αC-helix plays a crucial role in integrating the hydrophobic residues, making it a hub for allosteric regulation of kinase activity and the active conformation. The computational free-energy landscapes reported here illustrate novel design principles focusing on the important role of the hydrophobic spines. The relative stability of the spines could be exploited in future efforts to artificially engineer active-like but catalytically dead forms of protein kinases. Graphical abstract: Highlights: All-atom molecular dynamics simulations and umbrella sampling potential of mean force computations on Src tyrosine kinase activation Quantify the impact of activating and inactivating mutations of c-Src kinase A specific double-mutant can stabilize c-Src kinase into an active-like conformation while disabling the binding of ATP in the catalytic active site. Novel design principles to engineer active-like but catalytically dead forms of protein kinases